2005
DOI: 10.1212/01.wnl.0000183149.87975.32
|View full text |Cite
|
Sign up to set email alerts
|

Predicting gadolinium enhancement status in MS patients eligible for randomized clinical trials

Abstract: Gadolinium status can be predicted by a set of baseline variables, certainly when T2 burden of disease is included. These findings may benefit the design and statistical power of future randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…This finding supports the observation that the presence of Gd lesions is correlated with subsequent lesion activity. 21,22 In contrast, we showed that the favorable treatment effect of interferon beta-1b on subsequent lesion development per se was largely independent of the presence of active lesions at the time of the CIS (Table 3). This is in line with the fact that the treatment effect of interferon beta-1b on the conversion to CDMS was robust throughout the BENEFIT study population and numerically even more pronounced in patients without Gd enhancement on the initial MRI.…”
Section: Commentmentioning
confidence: 76%
See 1 more Smart Citation
“…This finding supports the observation that the presence of Gd lesions is correlated with subsequent lesion activity. 21,22 In contrast, we showed that the favorable treatment effect of interferon beta-1b on subsequent lesion development per se was largely independent of the presence of active lesions at the time of the CIS (Table 3). This is in line with the fact that the treatment effect of interferon beta-1b on the conversion to CDMS was robust throughout the BENEFIT study population and numerically even more pronounced in patients without Gd enhancement on the initial MRI.…”
Section: Commentmentioning
confidence: 76%
“…Were lost to follow-up in double-blind study 21 Did not enter extension study 10 Had no month 24 MRI in extension study 13…”
mentioning
confidence: 99%
“…All new white matter lesions go through this phase of enhancement that lasts between 2 and 8 weeks (Barkhof 1999). A number of studies have evaluated sex-based differences in the number of Gd-enhancing lesions in MS and most (Weatherby et al 2000;Pozzilli et al 2003;Tomassini et al 2005), but not all (Barkhof et al 2005) of these studies observed a higher number in women. However, the number of Gd-enhancing lesions correlates only weakly with concurrent EDSS scores and is thus not considered to be a good indicator of disease progression (Barkhof 1999).…”
Section: White Matter Changesmentioning
confidence: 99%
“…A number of studies have demonstrated that Gd enhancement is correlated with the occurrence of clinical relapses in MS (1)(2)(3). The number or volume of Gd-enhancing lesions is useful for evaluating biologically relevant treatment effects (4,5).…”
mentioning
confidence: 99%